The Application in Tax Violation Cases Involving Public Figures: A Legal and Criminological Analysis - Harly Clifford Jonas Salmon (PT. Anagata Sembagi Education, 2025)
The phenomenon of tax violations involving public figures shows the existence of structural vulnerabilities in the tax system that require regulatory strengthening. This study analyzes the application of the law in cases of tax violations by public figures through a normative juridical approach by examining the provisions of Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (HPP Law) and a number of related regulations. This study examines the position of tax norms, law enforcement mechanisms, and the relevance of criminological perspectives to the behavior patterns and motivations of violations committed by influential taxpayers. The HPP Law provides significant updates through improving compliance standards, strengthening administrative and criminal sanctions, and digitizing tax administration which has an impact on increasing the effectiveness of supervision. The discussion shows that law enforcement regulated by the HPP Law is more proportional, accountable, and oriented towards fiscal justice, so as to be able to narrow the gap for the manipulation of tax obligations by public figures. Criminological studies confirm that tax reform has succeeded in suppressing opportunistic factors through an increased risk of detecting violations. The results of the study concluded that the harmonization of regulations through the HPP Law has strengthened the integrity of the tax system and strengthened the state's efforts to build equal compliance for all taxpayers without discrimination.